Analysis of methods for the extension of wagon service life (Transport systems and technologies, 2019)
In the article the authors consider the most common methods of extending the service life of wagons, namely: control tests and methods of non-destructive testing. The task of control tests is an experimental verification of the conformity of the parameters of the strength of the design of the wagon to the requirements of normative documents. The control tests include: static vertical strength tests, dropping from wedges, typical collision strength tests. Performing non-destructive testing of properties and indicators of the object of control should not lead to its destruction or violation of the suitability of the object for use and operation. Methods of non-destructive testing are classified according to the following features: the nature of the interaction of physical fields or substances with the controlled object, primary informative indicators, methods of obtaining primary information. In the study of the technical condition of knots and parts of wagons, only 4 methods of non-destructive control are most widely used: visual, capillary, magnіtopowder, ultrasonic (ultrasonic thickness gauging).According to the results of the analysis in the article, one can highlight the disadvantages and advantages of control tests. The main advantage should include the possibility of distributing the results to a batch of wagons of one model and the year of construction, the main drawback - it is quite lengthy to conduct control tests (1-2 months) and decryption of the results (2-3 months).Having analyzed the methods of non-destructive testing, it has been shown that they enable to instantly determine the technical condition of the wagon and extend the service life or eliminate it from operation. The most effective and unpretentious non-destructive control method is MT because it, unlike the PT method, detects sub surface defects (up to 2 mm from the surface) and does not have the requirements for the surface roughness of the object of control, which in turn does not require the operator Conduct control of the definition of false defects.
Keywords: wagon, life extension, methods